Enhancing the movement of natural persons in the ASEAN region: Opportunities and constraints - Tereso S. Tullao; Michael Angelo A. Cortez (Asia-Pacific Research and Training Network on Trade (ARTNeT), 2006)
The overall objective of the movement of natural persons (MNP) in the ASEAN region is to contribute to expanding trade in services and to deepening economic integration. However, the regional movement of human resources has proceeded beyond the expansion of trade and has persisted in response to labor market imbalances.
Keywords: F1; 330; Movement of Natural Persons (MNP); ASEAN Framework Agreements on Services (AFAS)